Nonpoint source pollution regulation when polluters might cooperate - Katrin Millock; François Salanié (Fondazione Eni Enrico Mattei (FEEM), 1997)
We analyse the regulation of nonpoint source pollution. In particular, we study the use of peer monitoring to sustain co-operative abatement by a group of polluters. Delegation to a group of polluters has sometimes been proposed under a policy of so called voluntary abatement accords. By solving the problem of a regulator who a priori does not know whether agents are co-operative or not, we explain some features of voluntary abatement accords. The analysis shows that the policy measure proposed in the literature for nonpoint source regulation - an ambient tax - may not be efficient.
Keywords: D82; H41; Q25; Q28; 330; Peer monitoring; Co-operation; Voluntary abatement accords; Environmental regulation; Ambient tax; Incomplete information